2013
DOI: 10.1080/07347332.2013.798759
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Support Seeking and Race/Ethnicity in Posttraumatic Growth Among Breast Cancer Survivors

Abstract: Posttraumatic growth (PTG) after cancer can minimize the emotional impact of disease and treatment; however, the facilitators of PTG, including support-seeking, are unclear. We examined the role of support-seeking on PTG among 604 breast cancer survivors ages 40–64 from the Health Eating, Activity, and Lifestyle (HEAL) Study. Multivariable linear regression was used to examine predictors of support-seeking (participation in support groups and confiding in healthcare providers) as well as the the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
(62 reference statements)
1
15
0
1
Order By: Relevance
“…However, the research on social support and PTG in the context of life-threatening illness remains inconclusive. On the one hand, support seeking (Kent et al, 2013) and received social support (Schroevers, Helgeson, Sanderman, & Ranchor, 2010) were positively related to PTG among some cancer patients. Conversely, the link between social support and PTG was not found among cardiac patients (Sheikh, 2004) and other studies conducted on cancer patients (Sears, Stanton, & Danoff-Burg, 2003).…”
mentioning
confidence: 99%
“…However, the research on social support and PTG in the context of life-threatening illness remains inconclusive. On the one hand, support seeking (Kent et al, 2013) and received social support (Schroevers, Helgeson, Sanderman, & Ranchor, 2010) were positively related to PTG among some cancer patients. Conversely, the link between social support and PTG was not found among cardiac patients (Sheikh, 2004) and other studies conducted on cancer patients (Sears, Stanton, & Danoff-Burg, 2003).…”
mentioning
confidence: 99%
“…Essa categoria compreendeu apenas um estudo. Kent et al (2013) encontraram que o fato de participar de um programa de apoio e confiar nos profissionais de saúde foi associado ao maior crescimento pós-traumático. Como esse construto é definido como a mudança positiva que uma pessoa pode experimentar como resultado de seu processo de luta para sobreviver emocionalmente, a uma experiência traumática, pode-se afirmar que os grupos potencializam a elaboração psicológica do impacto dessas vivências e favorecem a assimilação das aprendizagens e benefícios que podem advir do contato com situações adversas.…”
Section: Resultsunclassified
“…PTG has been observed in a sample of not only cancer patients but also other people, such as those who experienced natural disaster (Nakagawa et al, 2014), husbands of breast cancer survivors (Weiss, 2004), the bereaved (Taku, Calhoun, Cann, & Tedeschi, 2008), parents of children with life-threatening disease (Forinder & Norberg, 2013), and people with HIV/AIDS (Milam, 2004). One study examining PTG among cancer survivors revealed that approximately 87% of them have experienced PTG at most; however, the prevalence rate varies depending on the characteristics of participants, such as age, gender, race, and the site or stage of cancer (Arpawong, Richeimer, Weinstein, Elghamrawy, & Milam, 2013;Brix et al, 2013;Crawford, Vallance, Holt, & Courneya, 2015;Danhauer et al, 2013;Kent et al, 2013;Lelorain, Bonnaud-Antignac, & Florin, 2010;Nenova, DuHamel, Zemon, Rini, & Redd, 2013;Wang et al, 2014;Wilson, Morris, & Chambers, 2014;Zebrack et al, 2014).…”
Section: Current Models Of Ptg and Hsbmentioning
confidence: 99%